Teluk Benoa dan laut Serangan Sebagai “laut peradaban” di Bali - I Putu Gede Suwitha (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This study aims to reveal the trade networks and dynamics of maritime history in the waters of Bali, especially in the 19th century. There is an interesting aspect in the study of maritime history in Bali namely the importance of Benoa Bay marine area to be the entrance to Bali since many centuries ago. Benoa Bay region directly opposite the Indian Ocean is also associated with Lombok and Bali Straits that become the entry point of the sea trade between Asia and Australia. The study used historical and ethnographic methods. The historical method as well as ethnographic were used to discuss maritime cultural dynamics to the community around the region of Benoa Bay of Bali waters. The results showed that Benoa Bay area turned into the arena of cultural interactions resulting in he mixed culture (mestizo) which produces a different customs from other regions. The occurrence of cross-cultural and civilization contacts put this region as a typical region or special zones outside the sphere of Islamization as the Sea of Civilization.